Native ambient mass spectrometry of intact protein assemblies directly from Escherichia coli colonies. Issue 48 (26th May 2022) - Du, Yuying; May, Robin C.; Cooper, Helen J.
Abstract : Electroporation combined with native liquid extraction surface analysis mass spectrometry allows analysis of intact protein assemblies directly from bacterial colonies. Abstract : Here, we demonstrate that by combining electroporation with native ambient mass spectrometry, it is possible to detect intact non-covalent protein complexes directly from bacterial colonies growing on agar. Homodimers HdeA and HdeB were identified, together with the 50 kDa Mn-bound superoxide dismutase homodimer, in addition to some previously undetected monomeric proteins.